(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article describes the relational framework of a non-profit organization for the management of which several keys have been hereby provided. To this end, firstly a definition of the non-profit organization as well as the concept of stakeholder, considered as descriptive instruments to draw up a strategic map of the relations will be introduced. Secondly, a presentation of the main actors, as well as of the different functions they can carry out, who intertwine with the non-profit organization, will be put forwards. Thereafter, the conceptualization of a complex relational framework, which goes beyond the usual preoccupation funding as well as this of the attention on the target populations, and the justification of the relevancy of what makes the thinking wealthy in this wider scope. Finally, some suggestion for the relationship management will be submitted based on five points: defining objectives, precision of stakeholders, the kind of relation and its priority, the global repercussions, the risks and benefits of present approach.